2001
DOI: 10.1143/jjap.40.1384
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Properties and Thermodynamic Stability of Sr(Ti1-x,Rux)O3 Thin Films Deposited by Inductive-Coupling-Plasma-Induced RF Magnetron Sputtering

Abstract: Sr(Ti 1−x ,Ru x )O 3 (STRO) epitaxial thin films were deposited on single-crystal SrTiO 3 (100) substrates using the inductivecoupling-plasma-induced RF magnetron sputtering method without oxygen. The electrical conductivity of STRO films increases with Ru concentration and levels of the Ru 4d states are observed in the band gap of SrTiO 3 by X-ray photoelectron spectroscopy (XPS) analysis. These results are consistent with those obtained by first-principles calculations. Thermodynamic stability increases with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…Simultaneously the lattice part disappeared completely from the Sr3d spectrum in both cases. Similar ruthenium oxidation and reduction processes were presented before by Hartmann et al, 42 for metallic Ru thin films annealed in air, and Ohara et al, 46 for Sr͑Ti 1−x Ru x ͒O 3 thin films annealed in hydrogen. The presented Ru3d spectra always consisted of a low binding energy line related to metallic ruthenium and one or more lines, shifted by 1 -2.5 eV to higher binding energies, related to oxidized ruthenium.…”
Section: -2supporting
confidence: 80%
See 1 more Smart Citation
“…Simultaneously the lattice part disappeared completely from the Sr3d spectrum in both cases. Similar ruthenium oxidation and reduction processes were presented before by Hartmann et al, 42 for metallic Ru thin films annealed in air, and Ohara et al, 46 for Sr͑Ti 1−x Ru x ͒O 3 thin films annealed in hydrogen. The presented Ru3d spectra always consisted of a low binding energy line related to metallic ruthenium and one or more lines, shifted by 1 -2.5 eV to higher binding energies, related to oxidized ruthenium.…”
Section: -2supporting
confidence: 80%
“…Annealing of Sr͑Ti 1−x Ru x ͒O 3 in hydrogen caused the oxide line to shift to lower binding energies and finally to vanish, while the metal line appeared and grew in size. 46 In this case a reduction clearly took place with the presence of intermediate oxidation states.…”
Section: -2mentioning
confidence: 94%
“…Furthermore, Gupta, Hussey, and Shaw (1996) showed that epitaxial growth of thin films of SrTi 1Àx Ru x O 3À by PLD at low oxygen partial pressure [< 10 À3 mTorr (necessary to make possible the usage of standard RHEED during deposition)] assisted by atomic oxygen, clearly exhibit degraded magnetic and electronic properties. The degree of degradation was later found to be dependent on the exact initial composition (Ohara et al, 2001).…”
Section: Influence Of Stoichiometrymentioning
confidence: 98%
“…MS has been used to grow a variety of epitaxial oxides of interest as optical waveguides, [217] light emitters, [218][219][220][221] capacitor dielectrics, [222,223] high-T c superconductors, [224][225][226][227][228] photocatalysts, [229] gas sensors, [83] ferroelectrics, [230][231][232][233] piezoelectrics, [46,234] conductive oxides, [235][236][237][238][239] gate dielectrics, [29,[240][241][242][243][244] magnetoresistive materials, [245][246][247][248][249][250][251][252][253][254][255][256][257] general purpose insulators, [258,259] magnetic insulators, [260,261...…”
Section: Magnetron Sputteringmentioning
confidence: 99%